Digital Tafsir Digital dalam Era Media Sosial: Studi Tematik QS Asy-Syura ayat 52 dan QS al-Qashash ayat 56 pada Akun Instagram @tafsiralmisbah.digital: Studi Tematik QS Asy-Syura ayat 52 dan QS al-Qashash ayat 56 pada Akun Instagram @tafsiralmisbah.digital - Khoirurrizqi Addimyathi; Qonita Zakiyah; M. Badrus Sholeh; Mokh Syaroni (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2025)
This study aims to analyze the practice of social media-based interpretation of the Qur'an through the Instagram account @tafsiralmisbah.digital, focusing on the interpretation of two thematic verses related to the concept of guidance: QS Ash-Shura, verse 52, and QS al-Qashash, verse 56. This study employs a qualitative-descriptive approach, incorporating netnography and content analysis methods, to investigate the pattern of digital da'wah delivery and the transformation of interpretation methods in the social media era. The results of the study show that the @tafsiralmisbah.digital account applies a popular interpretation model that combines spiritual narratives, visual approaches, and communicative and reflective language. The interpretation of the hadith verse is presented contextually through a dualistic approach, combining the guidance of irsyad and taufiq, as explained in Tafsir al-Misbah. In addition, social media serves as a means of participatory interpretation, where users not only passively receive messages but also actively engage through comments, emotional responses, and real-world actions. This study concludes that digital interpretation can be an effective means of disseminating the messages of the Qur'an, provided it is done responsibly, while upholding the scientific principles and ethics of da'wah. These findings contribute to the discourse on religious digital literacy and social media-based da'wah strategies in the contemporary era.